Efek Kebijakan Moneter Terhadap Return Harga Emas Di Indonesia - Abdul Khaliq (Universitas Bunda Mulia, 2018)
This studyobserves the short-run and long-run relationship between monetary policies andgold price return movements in Indonesia. Using monthly data over the period 1997M09-2017M10,the empirical findings are carried out by utilizing error correction model (ECM)derived from single quadratic cost function to provide evidence in favor of relationship between nominal effective exchange rate, interest rate, and money supplyand gold price return movements.The empirical evidence suggests that the ECM estimates well characterize how the nominal effective exchange rate relates to the gold price return movements, both in the long-run and short-run. Moreover, money supply and interest rate only have negative and statistically significant effects on price gold return movements in the long run. These results imply that observing nominal effective exchange rate can help predict gold price return movements in Indonesia, which would significantly help monetary authorities in optimizing monetary policy.Keywords : Gold Price Return, Monetary Policies, Error Correction Model (ECM)